GRENOULIE’S PSYCHOPATHIC BEHAVIOUR DEPICTED IN PERFUME: THE STORY OF A MURDERER - IKA AYU SULISTYANINGRUM, ANNISA (LANGUAGE HORIZON, 2019)
Psychopath is an interesting form of mental disorder to discuss. Many films show psychopathic behavior which is considered as very cruel and sadistic yet still looks beautiful. Through this study the author wants to invite the reader to recognize the signs of someone who has a tendency to psychopathic behavior. One of the most famous works containing this topic is Perfume: The Story of a Murderer written by Patrick Suskind. Psychopathic behavior displayed in this work is in a character named Jean-Baptise Grenoulie who easily took the lives of 26 virgin girls as perfume ingredient. This study focuses on Grenoulies psychopathic and factors that motivate him to perform psychopathic actions. The theory uses Hervey Cleckleys Mask of Sanity theory which mentions psychopathic characteristics. Combined with the theory of needs by humanist psychologist Abraham Maslow. By using psychoanalytic approach, the data is taken from the novel Perfume: The Story of a Murderer. Data were obtained using 16 psychopathic signs belonging to Cleckley which were then adjusted to the signs that emerged from Grenouliet. Which later on writer searched for background or motivation in performing the behavior. This study found that Grenoulie had 13 psychopathic signs from the 16 that had been mentioned. Then the factors underlying the psychopathic behavior are that many of his basic needs are not being met, so those feeling accumulate to the need for actualize himself. It was in this way of actualizing oneself that Grenoulie was referred to as a Psychopath. Keywords: Psychopath, Needs, Behavior, Perfume